Robust synthesis of highly charged superparamagnetic Fe3O4 colloidal nanocrystal clusters for magnetically responsive photonic crystals. (18th August 2021) - Pan, Liting; Peng, Zhuo; Yu, Hairong; Liang, Ting; Cheng, Changjing
Abstract : Herein, highly charged superparamagnetic Fe3 O4 colloidal nanocrystal clusters with uniform and widely tunable sizes have been synthesized by a robust and easily scalable solvothermal method for magnetically responsive photonic crystals. Abstract : Highly charged superparamagnetic Fe3 O4 colloidal nanocrystal clusters (CNCs) with uniform and widely tunable sizes can be magnetically assembled into responsive photonic crystals to exhibit rapid and reversible brilliant structural color changes under an external magnetic field. We herein investigated a robust and easily scalable solvothermal synthesis of CNCs using anionic polyelectrolyte, poly(4-styrenesulfonic acid- co -maleic acid) sodium salt (PSSMA), as the capping ligand. The molar ratio of the two acid segments was found to greatly affect the surface charges of the resulting CNCs and thus their photonic properties, with a higher surface charge for particles synthesized with ligands of a higher SS/MA ratio. Moreover, the dosage of PSSMA (3 : 1) and the molar ratio of acetate ions to iron ions (Ac − /Fe 3+ ) in the reactants also had significant effects on the sizes and surface charges of the obtained CNCs and thus their photonic properties. These parameters can be easily optimized to produce CNCs with strong optical diffractions and wide tunability of diffraction wavelengths in various solvents in response to an external magnetic field. This synthetic method can be easily scaled up to 20 folds, producing ∼3.32 g of nanoparticles in one batch with excellent photonic properties. This work is expected to impact significantly the field of magnetically responsive photonic structures by providing easy access to high-quality superparamagnetic colloidal nanoparticles.